#TITLE_ALTERNATIVE# - NOOR PRAWITA (NIM 13202161), FAT'HAH
Packet routing analysis in a wireless mesh network, is needed to know the information about which virtual wireless interface is being used for sending some data packets. The importance of this analysis, for example, in ITB computer network that has a policy about using of an username for accessing through ITB proxy server, is not allowed from several IP address concurrently. This research using seven nodes (1 sender, 1 receiver, and 5 intermediaries) based on three scenarios. The sender node, that was connected to several intermediary nodes, sending ping request to the receiver node. Based on ping request log inside the receiver node, can be concluded that when a sender node, that has several virtual wireless interfaces, sent data packet to a receiver node that placed on the same network with one of its virtual wireless interface, it used the virtual wireless interface that placed on that same network too. While on the other scenario, when a sender node, that has several virtual wireless interfaces, sent data packet to a receiver node that placed outside all of its virtual wireless interfaces, it used virtual wireless interface that has default gateway and metric value as typed in the Route Table. Whereas on the third scenario, when a sender node, that connected to two or more ad-hoc networks based on Windows XP operating system, couldn't sent data packet to the receiver node. It happened because there are more than one intermediary nodes that has same IP address (192.168.0.1).